EFFECT OF KANGFUXIN LIQUID ON INTESTINAL BARRIER IN ELDERLY PATIENTS WITH MECHANICAL VENTILATION IN THE INTENSIVE CARE UNIT - Hongwei, Zhang; Liyou, Wei; Gang, Zhao; Shuzheng, Liu; Jing, Zhang (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background:Kangfuxin Liquid is extracted from America periplaneta, which is effective for treating gastrointestinal ulcers and repairing gastrointestinal mucosal tissue. The purpose of this study is to explore the effect of Kangfuxin Liquid on improving intestinal barrier dysfunction in elderly patients using mechanical ventilation and effectively restraining the concentration of D-lactate.Materials and Methods: Elderly patients with mechanical ventilation were selected, and divided into “control” and “treatment” groups by using a random number table. Patients in both groups were given conventional treatment. Patients in “treatment group” additionally received Kangfuxin Liquid. At baseline and at 3, 7days following treatment, recordings for the concentration of D-lactate, intra-abdominal pressure (IAP) and bowel sounds were conducted. The duration of mechanical ventilation, the time of stay in ICU and the mortality rate during 28 days were recorded. Results: At baseline, there were no significant differences in the terms of the concentrations of D-lactate, IAP and bowel sounds in the two groups (P>0.05). At 3 and 7days following treatment, the concentration of D-lactate, IAP and bowel sounds in the “treatment group” were better than those in the “control group”. The differences were statistically significant (P<0.05). The duration of mechanical ventilation and the time of stay in intensive care unit (ICU) in the treatment group were less than those in the control group (P<0.05).Conclusion: Kangfuxin Liquid can restrain the concentration of D-lactate, improves intestinal mucosal permeability, enhances the intestinal barrier, and improves the condition in elderly patients with mechanical ventilation.